2022
DOI: 10.3389/fped.2022.812246
|View full text |Cite
|
Sign up to set email alerts
|

Lung Ultrasound to Detect Pneumothorax in Children Evaluated for Acute Chest Pain in the Emergency Department: An Observational Pilot Study

Abstract: BackgroundSpontaneous pneumothorax is a relatively uncommon and poorly studied condition in children. While several protocols have been developed to evaluate the use of lung ultrasound for dyspneic adult patients in the emergency department, no specific guidelines are present for pediatric emergency physicians.ObjectivesWe prospectively analyzed children with acute chest pain and clinical suspicion of pneumothorax evaluated at the pediatric emergency department.MethodsWe consecutively enrolled children aged 5–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
(40 reference statements)
0
5
0
1
Order By: Relevance
“…Scialanga et al (8) revealed the "barcode sign" in 13 patients, and a lung point, indicative of PNX, was present in 12 (92.3%) of the patients. In five (38.5%) patients with a small PNX, Between the anterior axillary and parasternal lines on the anterior chest surface was the lung point.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scialanga et al (8) revealed the "barcode sign" in 13 patients, and a lung point, indicative of PNX, was present in 12 (92.3%) of the patients. In five (38.5%) patients with a small PNX, Between the anterior axillary and parasternal lines on the anterior chest surface was the lung point.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, in pneumothorax group, all patients (100%) with pneumothorax had absence of B lines, lung sliding, and lung pulse sign and absent A line, while 37.5% of patients with collapse had lung point sign. Scialanga et al (8) assessed children experiencing acute chest discomfort to determine how accurate LUS was in identifying PNX. Thirty of the seventy-seven children (or 39%) suffered thoracic trauma; twenty of the seventy-seven children (or 26%) had pneumonia, with or without pleural effusions; and thirty of the seventy-seven children (or 39%) had interstitial lung disease, such as viral bronchitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis of PMS is generally established by chest X-ray, with chest CT being performed only in complicated cases. Other radiological studies, such as ultrasound, are rarely performed but can help the diagnosis in children [ 17 , 18 ]. Chest CT representative findings in COVID-19 are represented by bilateral ground-glass opacities with or without consolidation involving posterior and peripheral lungs.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary system-related chest pain is also not highly prevalent, accounting for 1.82–12.78% [ 1 , 9 , 12 , 14 , 15 , 16 , 17 , 31 ], with common causes including pneumothorax, asthma, pneumonia, and the less common pneumomediastinum [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Some of these diseases can be potentially life-threatening, such as tension pneumothorax.…”
Section: Etiology Of Chest Pain In Children and Adolescentsmentioning
confidence: 99%